Effect of effort‐reward imbalance and burnout on infection control among Ecuadorian nurses. (7th November 2017) - Colindres, C.V.; Bryce, E.; Coral‐Rosero, P.; Ramos‐Soto, R.M.; Bonilla, F.; Yassi, A.
Abstract : Background: Nurses are frequently exposed to transmissible infections, yet adherence to infection control measures is suboptimal. There has been inadequate research into how the psychosocial work environment affects compliance with infection control measures, especially in low‐ and middle‐income countries. Aim: To examine the association between effort‐reward imbalance, burnout and adherence to infection control measures among nurses in Ecuador. Introduction: A cross‐sectional study linking psychosocial work environment indicators to infection control adherence. Methods: The study was conducted among 333 nurses in four Ecuadorian hospitals. Self‐administered questionnaires assessed demographic variables, perceived infection risk, effort‐reward imbalance, burnout and infection control adherence. Results: Increased effort‐reward imbalance was found to be a unique incremental predictor of exposure to burnout, and burnout was a negative unique incremental predictor of nurses' self‐reported adherence with infection control measures. Discussion: Results suggest an effort‐reward imbalance‐burnout continuum, which, at higher levels, contributes to reduce adherence to infection control. The Ecuadorean government has made large efforts to improve universal access to health care, yet this study suggests that workplace demands on nurses remain problematic. Conclusion: This study highlights the contribution of effort‐reward‐imbalance‐burnout continuum to the chain of infection by decreased adherence to infection control of nurses. Implications for Nursing Policy: Health authorities should closely monitor the effect of new policies on psychosocial work environment, especially when expanding services and increasing public accessibility with limited resources. Additionally, organizational and psychosocial interventions targeting effort‐reward imbalance and burnout in nurses should be considered part of a complete infection prevention and control strategy. Further study is warranted to identify interventions that best ameliorate effort‐reward imbalance and burnout in low‐ and middle‐income settings.